Long-term characteristics of prestressing force in post-tensioned structures measured using smart strands - Kim, Sang Hyun; Park, Sung Yong; Jeon, Se Jin (Applied Sciences (Switzerland), 2020)
The proper distribution of prestressing force (PF) is the basis for the design of prestressed concrete (PSC) structures. However, the PF distribution obtained by predictive equations of prestress losses has not been sufficiently validated by comparison with measured data due to the poor reliability and durability of conventional sensing technologies. Therefore, the Smart Strand with embedded fiber optic sensors was developed and applied to PSC structures to investigate the long-term characteristics of PF distribution as affected by concrete creep and shrinkage. The data measured in a 20 m-long full-scale specimen and a 60 m-long PSC girder bridge were analyzed by comparing them with the theoretical estimation obtained from several design equations. Although the long-term decreasing trend of the PF distribution was similar in the measurement and theory, the equation of Eurocode 2 for estimating the long-term prestress losses showed better agreement with the measurement than ACI 209R and ACI 423.10R did. This can be attributed to the more refined form of the predictive equation of Eurocode 2 in dealing with the time-dependency of the PF. The study results also confirmed the need to compensate for the temperature variation in the long-term monitoring to derive the actual mechanical strain related to the PF. We expect our developed Smart Strand to be applied practically in PF measurement for the reasonable safety assessment and maintenance of PSC structures by improving several of the existing drawbacks of conventional sensors.
Keywords: Fiber bragg grating; Fiber optic sensor; Prestress loss; Prestressed concrete; Prestressing force; Prestressing tendon; Strand